Relationship between auditory memory and the reading and writing process in a primary school population. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2022)
INTRODUCTION: This research analyzes the relationship between auditory memory and the reading and writing process in the elementary school population, as well as relevant information about the evaluation methods of the mentioned variables. METHODS: For the elaboration of this article, the systematic review methodology was used according to Prisma parameters, defined as a form of research that uses as a source of data the literature on a certain topic. This type of research provides a summary of the evidence related to a specific research strategy, through the application of explanatory and systematized methods of search, critical appraisal and synthesis of the selected information RESULTS: The results are the combination and structuring of the different documents selected through the prism methodology, through which a considerable number of articles were found that were important at the time of organizing the studies necessary for the research.ANALYSIS AND DISCUSSION: Auditory memory is therefore an important factor in reading performance, since beyond the influence of processing, which predicts spelling and decoding, it is reported that there is a direct and moderate relationship between some writing tasks and memory types. CONCLUSIONS: According to the exhaustive search on the relationship between auditory memory and the reading and writing process, it can be stated that in most studies there is correlation between the study variables.
Keywords: Auditory Memory; Reading; Writing; Learning; Auditory Perception; Evaluation